Peningkatan Pengetahuan Mengenai Peran Nutrisi Dalam Sistem Imun - Arviani, Arviani; Ferly , Ferli Eko Kurniantoro (ABDIMAS Madani, 2024)
The pandemic began with the emergence of a new coronavirus in Wuhan, China. One way to prevent the transmission of this virus is by consuming nutritious foods that can boost the body's immunity. The immune system or the body's defense system is the body's ability to fight infections against bacteria or virulent factors. Consuming food rich in nutrients such as vitamins and minerals is important for enhancing the immune system. This community service aims to provide education to the community about food that can help improve the immune system. The youth of Nyamplung village have diverse educational backgrounds. Most have worked in several factories located in Yogyakarta. High interaction allows for exposure to bacteria and viruses, so it is necessary to boost immunity by consuming foods rich in minerals and vitamins. This community service activity is carried out with a community - based approach through directed discussion forums. The target is the youth in Nyamplung Village, Srimulyo Village, Piyungan District, Bantul Regency, Yogyakarta. The initial stage involved administering a pre-test to measure the level of knowledge. The post-test results of this community service program indicated an increase in the knowledge of the youth in Dusun Nyamplung about the importance of consuming nutritio us food to enhance the immune system through community-based directed discussion forums